(untitled) (Journal of Libya for geographical studies, 2025)
Northwestern Libya, located within the subtropical zone, faces numerous environmental and human-induced hazards, including low rainfall, recurring droughts, sandstorms, and advancing desertification. These are compounded by human risks such as wars, traffic accidents, fires, and other disasters. This study aimed to assess public awareness of these pressing and potential hazards in the Tripoli region. A descriptive-analytical approach was adopted, using a structured survey administered to a sample of 143 individuals aged 20–70, with educational levels ranging from secondary school to doctoral degrees. The statistical analysis confirmed that desertification is perceived as an ongoing crisis, regardless of educational background. A significant relationship was found between education level and awareness of groundwater depletion risks. No statistically significant differences were noted between age groups regarding awareness of seawater intrusion or aquifer depletion. Interestingly, women showed greater awareness of agricultural drought than men and were more concerned about traffic accidents, inflation, and civil war (p ≤ 0.05). However, the gender difference in awareness of unemployment issues was not statistically significant. Younger respondents (under 40) demonstrated significantly higher concern about limited job opportunities (p ≤ 0.01(.